Introduzione: La rappresentazione del lavoro nelle raccolte di racconti dagli anni Ottanta a oggi (Ticontre. Theory Text Translation, 2021)
This introduction offers a short overview of the latest multi-authorial collections of short stories dedicated to the theme of work and reflects on why this production deserves attention from literary criticism. It also identifies and underlines the main features emerged from the contributions collected in this monographic section.